A Spotlight of Co-creation and Inclusiveness of Public Open Spaces - Šuklje Erjavec, Ina; Ruchinskaya, Tatiana (CyberParks – The Interface Between People, Places and Technology: New Approaches and Perspectives, 2019)
This chapter focuses on co-creation as the way to engage different stakeholders with everyday urban environments based on equality, diversity and social cohesion. It presents the relationship of co-creation and inclusiveness of public open spaces together with different aspects of co-creation related to issues of publicness and space. It discusses why and how co-creation must take into consideration the characteristics of the comprehensive spatial development processes. It suggests that co-creation is a wider concept than co-design and is a multistage process that contributes to inclusive public spaces, providing measures for social sustainability of place. This chapter argues that digital tools may help to overcome challenges of co-creation and provide an opinion on the contribution of digital technologies to the co-creation process by engaging people in the design, use and management of public spaces, providing new resources for interaction and users’ empowerment. For that it presents an overview of the possible contribution of digital technologies to support inclusiveness of the co-creation processes that is structured by typologies of digital tools and their possible interlinking with the steps of the co-creation process. To improve the understanding of such possibilities it critically addresses strengths and weaknesses of using digital tools for co-creation and inclusiveness and provides recommendations for their further development.
Keywords: Co-création; Inclusion; Outil numérique

Innovation sociale et développement territorial - Klein, Juan-Luis (Érès, 2014)

Cité Studio Montréal (CitéStudio Montréal)
CitéStudio Montréal est un trait d’union entre l’expertise des employé·e·s de la Ville de Montréal et la créativité des étudiant·e·s universitaires.

Chaire In.SITU en stratégies intégrées Transports-Urbanisme - Chair In.SITU, ESG USQAM (Chaire In.SITU Innovations en stratégies intégrées transport-urbanisme, 2021)
Site de la Chaire In.SITU | Recherche-innovation en stratégies intégrées Transports-Urbanisme de l'ESG UQAM Accès à des publications académiques, rapports et études, et les Cahiers In.SITU Cahier 1 - Les conditions de réussite d’un TOD : Retour sur la journée de réflexion du 28 janvier 2016 (TOD : transit-oriented development) Cahier 2 - Vivre et se déplacer, d’hier à aujourd’hui Montréal et Boucherville en exemples Cahier 3 - Portrait des disparités en matière de mobilité dans l’agglomération de Montréal Cahier 4 - Étude sur les facteurs et politiques de mobilité durable : le cas de la dépossession et réduction de l’usage de l’automobile Cahier 5 - La gestion de la demande : Revue des pratiques Cahier 6 - Inventaire illustré et raisonné de la gestion de la demande Cahier 7 - La gestion de la demande : analyse critique d’un registre d’action collective
Keywords: Développement Durable-Responsabilité Sociale (DD-RS); Libre accès; Mobilité; Montréal; Québec; Transport; Urbanisme

Social innovation for a circular economy in social housing - Marchesi, Marianna; Tweed, Chris (Sustainable Cities and Society, 2021)
This study explored how social housing communities can contribute to the transition to a circular economy (CE) in cities. The CE promotes ways for rethinking and reshaping current practices of producing and consuming to enhance resource efficiency while satisfying our needs to enable us to prosper sustainably. Resource efficiency in cities relies on production and consumption patterns that are connected to people behaviours. Up to now, the CE has mainly concentrated on different levels of technological system innovations with limited attention to social practices and behavioural change. On the other side, communities and groups of interest show playing a crucial role in the promotion of sustainable practices through initiatives of social innovation (SI). Through case study analysis and comparison, the project investigated contemporary SI initiatives implemented by urban communities and groups of interest aiming at promoting alternative production-consumption practices. Seven types of SI for resource circularity have been identified. Based on this typology, the study defined potential opportunities, benefits and challenges for social housing communities. These findings also highlighted a complementary role that SI can play in the CE implementation in cities. Therefore, the project suggested the introduction of emerging SI concepts into the current CE approach to support development.
Keywords: Réservé UdeM; Économie circulaire

Analyzing Citizen Participation and Engagement in European Smart Cities - Cortés-Cediel, María E.; Iván, Cantador; Rodríguez, Bolívar Manuel Pedro (Social Science Computer Review, 2021)
With the advent of smart cities (SCs), governance has been placed at the core of the debate on how to create public value and achieve a high quality of life in urban environments. In particular, given that public value is rooted in democratic theory and new technologies that promote networking spaces have emerged, citizen participation represents one of the principal instruments to make government open and close to the citizenry needs. Participation in urban governance has undergone a great development: from the first postmodernist ideals of countering expert dominance to today’s focus on learning and social innovation, where citizen participation is conceptualized as co-creation and co-production. Despite this development, there is a lack of research to know how this new governance context is taking place in the SC arena. Addressing this situation, in this article, we present an exhaustive survey of the research literature and a deep study of the experience in participative initiatives followed by SCs in Europe. Through an analysis of 149 SC initiatives from 76 European cities, we provide interesting insights about how participatory models have been introduced in the different areas and dimensions of the cities, how citizen engagement is promoted in SC initiatives, and whether the so-called creative SCs are those with a higher number of projects governed in a participatory way.
Keywords: Co-création; Co-production; Europe; Modèle participatif; Nouvelles technologies; Projets participatifs; Réservé UdeM; Urbanisme; Villes intelligentes

Laboratoires vivants en innovation sociale et coconstruction des connaissances dans les villes : les cas du TIESS (Montréal) et de l’OBISF (Florianópolis) - Magalhaes, Thiago; Camus, Annie; Andion, Carolina; Tello-Rozas, Sonia (Revue Organisations & territoires, 2020)
Le débat sur le rapport entre l’innovation sociale et les villes s’est élargi au cours des dernières décennies. Ce débat met en évidence l’intérêt suscité par les processus de coconstruction des savoirs dans les laboratoires vivants en innovation sociale (LVIS). Cet article a pour objectif de présenter une approche conceptuelle et analytique du traitement des LVIS, ainsi que de décrire et de mettre en perspective deux expériences de mise en oeuvre de LVIS dans les villes : l’Observatoire de l’innovation sociale de Florianópolis (OBISF) au Brésil et Territoires innovants en économie sociale et solidaire (TIESS) à Montréal au Canada. Bien qu’ils émergent dans des réalités et des contextes différents avec des méthodologies de mise en oeuvre spécifiques, qui sont présentées dans le texte, la discussion et l’analyse des deux cas apportent des pistes d’apprentissage sur les défis et les perspectives quant à la coconstruction des connaissances visant à renforcer les dynamiques d’innovation sociale à l’échelle d’une ville.
Keywords: Brésil; Canada; Co-construction; Laboratoire vivant; Réservé UdeM; Urbanisme; Économie sociale; Économie solidaire

A dual-functional social innovation process model for low-cost houses through university-enabled initiative - Belayutham, Sheila; Ibrahim, Che Khairil Izam Che; Zulkifli, Assrul Reedza; Ibrahim, Norhati (Construction Innovation-England, 2019)
The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching-learning. Design/methodology/approach This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching-learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching-learning and design-construct innovation. Originality/value The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching-learning and research development), is a breakthrough for further diffusions of social innovation by universities.
Keywords: Asie; Enseignement; Innovation sociale; Recherche; Rôle des universités; logement

Playing with the Rules of the Game: Social Innovation for Urban Transformation - Thompson, Matthew (International Journal of Urban and Regional Research, 2019)
Innovation is perhaps the buzzword in local economic development policy. Associated narrowly with neoliberal ideas, conventional notions of innovation—like its capitalocentric counterparts, enterprise and entrepreneurialism—may promise higher productivity, global competitiveness and technological progress but do not fundamentally change the ‘rules of the game’. In contrast, an emerging field reimagines social innovation as disruptive change in social relations and institutional configurations. This article explores the conceptual and political differences within this pre‐paradigmatic field, and argues for a more transformative understanding of social innovation. Building on the work of David Graeber, I mobilize the novel constructs of ‘play’ and ‘games’ to advance our understanding of the contradictory process of institutionalizing social innovation for urban transformation. This is illustrated through a case study of Liverpool, where diverse approaches to innovation are employed in attempts to resolve longstanding socio‐economic problems. Dominant market‐ and state‐led economic development policies—likened to a ‘regeneration game’—are contrasted with more experimental, creative, democratic and potentially more effective forms of social innovation, seeking urban change through playing with the rules of the game. I conclude by considering how the play–game dialectic illuminates and reframes the way transformative social innovation might be cultivated by urban policy, the contradictions this entails, and possible ways forward.
Keywords: Europe; Réservé UdeM; UK

Décentralisation à la française et innovation sociale : un compromis impossible - Landel, Pierre-Antoine; Pecqueur, Bernard (Économie et Solidarités, 2014)
Notre questionnement porte sur le profond décalage entre l'évolution de la pensée économique et les pratiques politiques issues de la décentralisation. Notre hypothèse met de l’avant que les logiques politiques mobilisées dans le cadre de ces réformes ne permettent pas d’accompagner le tournant territorial de l’économie (Pecqueur, 2006; Landel et Pecqueur, 2016). La difficulté des collectivités locales à prendre en compte et à accompagner l’innovation sociale témoigne de ces décalages. Pourtant, sous l’impulsion de l’État, de nouvelles formes de coordination s’affirment, parmi lesquelles on peut citer les pôles territoriaux de coopération économique (PTCE). Ils méritent d’être observés au regard de leur capacité à accompagner de nouvelles formes de développement territorial.
Keywords: Décentralisation économique; Réservé UdeM